Aspirin eugenol ester affects ileal barrier function, inflammatory response and microbiota in broilers under lipopolysaccharide-induced immune stress conditions - Zhang, Ruilin; Bai, Dongying; Zhen, Wenrui; Hu, Xiaodi; Zhang, Haojie; Zhong, Jiale; Zhang, Yi; Ito, Koichi; Zhang, Bingkun; Yang, Yajun; Li, Jianyong; Ma, Yanbo (Frontiers in Veterinary Science, 2024)
The aim of this study was to investigate the effects of aspirin eugenol ester (AEE) on ileal immune function in broilers under lipopolysaccharide (LPS)-induced immune stress. 240 one-day-old male Arbor Acres chicks were randomly divided into four groups (saline, LPS, saline+AEE and LPS+AEE) with six replicates of ten broilers each. The saline group and LPS group were fed the normal diet, while the other two groups received normal diet plus 0.1g/kg AEE. Broilers in the LPS and LPS+AEE groups were injected intraperitoneally with 0.5 mg/kg B.W LPS in saline for seven consecutive days beginning at 14 days of age, while broilers in the saline and saline+AEE groups were injected with saline only.The results showed that AEE improved the ileal morphology and increased the ratio of villus height to crypt depth of immune-stressed broilers. LPS-induced immune stress significantly reduced the expression of the genes for the tight junction proteins occludin, zonula occludens-1 (ZO-1), claudin-1 and claudin-2, in the ileum, while AEE significantly up-regulated the expression of these genes.Compared with the saline group, the LPS-treated chickens showed significantly increased mRNA expression of the inflammatory factors tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), interleukin-10 (IL-10), cyclooxygenase-2 (COX-2) and microsomal Prostaglandin E Synthesase-1 (mPGES-1) in the ileum, while they were significantly decreased by AEE supplementation. In addition, analysis of the ileal bacterial composition showed that compared with saline and LPS+AEE groups, the proportion of Firmicutes and Lactobacillus in the LPS group was lower, while the proportion of Proteobacteria and Escherichia-Shigella was higher. Similarly, Line Discriminant Analysis Effect Size (LEfSe) analysis showed that compared with the LPS group, Brevibacillus was dominant in the saline group, while the LPS+AEE group was rich in Rhizobium, Lachnoclostridium, Ruminococcaceae, Faecalibacterium, Negativibacillus, Oscillospiraceae, and Flavonifractor.These results indicate that dietary supplementation with 0.1g/kg AEE could protect the intestinal health by improving the intestinal villus morphology, enhancing the expression of tight junction genes and alleviating inflammation to resist the immune stress caused by LPS stimulation in broilers, and the mechanism may involve COX-2-related signal transduction and improved intestinal microbiota composition.